VD_FINDINFO HC / 2011 / 252 vom 11. Mai 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, RELATIONS PERSONNELLES, PROTECTION DE L'ENFANT, INTÉRÊT DE L'ENFANT | 176 al. 3 CC, 273 al. 1 CC, 273 al. 2 CC, 274 al. 2 CC, 308 al. 1 let. b CPC (CH)